Megalithic biographies. From partial closures to total closures and from single sealing to double sealing - Dominique Jagu; Claude Masset (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In five megalithic monuments in the Paris Basin, major structural rearrangements occurred from the Neolithic, involving displacements and removals of orthostats. The use of these monuments as tombs was periodically interrupted, possibly – but not necessarily – in conjunction with deposits of generally thin "underlayers", though at times these could also be relatively thick. Primary or secondary burials could co-occur or sometimes follow each other, in relation to these "underlayers". At times, an entire burial layer was almost completely eliminated. At two of these sites, evidence shows that heavy "cover slabs" were put in place only after burials had ceased, as a gesture of permanent closure: prior to their installation, only a lightweight, water-tight cover had been present. Although permanently closed, these megalithic structures continued to be visited for some time until they were sealed again, this time with a clearly destructive intention associated with their final abandon.